Tumor Recurrence and Drug Resistance Properties of Side Population Cells in High Grade Ovary Cancer - Zhang, Q.-H.; Dou, H.-T.; Xu, P.; Zhuang, S.-C.; Liu, P.-S. (Drug Research, 2015)
Introduction: The presence of subset of cancer stem cells (CSCs) called “Side population” (SP) cells has been identified in several solid tumors, responsible for treatment failure especially chemotherapy, and cancer relapse. The present study was aimed to isolate and characterize cancer stem like cells side population cells from high grade ovarian cancer.Methods: The collected cancer samples were analyzed for presence of SP cells by FACS using Hoechst 33342 exclusion technique. Further the FACS sorted SP and non-SP cells were subjected to analysis of stem cell surface protein expression by western blot and immunocytochemistry, drug resistance and sphere formation assay.Results: By FACS, we have identified 3.7% of cancer stem cell like side population cells in ovarian cancer whose prevalence was reduced to 0.5% upon treatment with verapamil an inhibitor of ABC transporter. Further, these sorted SP cells showed over expression of ABCG2 (ABC transporter), stem cell proteins such as CD144, CD44, EpCAM and antiapoptotic factor Bcl-2. Also the SP cells showed high resistance to chemotherapy drugs, have high survival rate and they are highly potential to form tumor spheres.Conclusion: Our data suggest that ovarian cancer contain small sub-population of side population cells which shares some characteristics of stem cells. The co-expression of ABC transporters and stem cells surface markers in SP cells may associate with resistance to chemotherapeutic agents, apoptosis and also supports a role for these cells in tumor recurrence, metastasis and invasion.
Keywords: cancer stem cells; apoptosis; chemotherapy; tumor recurrence; side population cells